SAFE BEHAVIOR ANALYSIS OF WORKERS WITH ABC (ACTIVATOR-BEHAVIOR-CONSEQUENCE) MODEL - Luthfi Rizky Affandhy; Neffrety Nilamsari (Universitas Darussalam Gontor, 2017)
One way of reducing occupational accidents is by implementing BBS program and the goal is by changing “at risk” behavior to safe behavior. The unsafe actions is likely driven by unawareness, ignorance, and incompetence of the workers to commit safe behavior. As the result, analysis on workplace safety behavior, the activator-behavior-consequence (ABC) model was applied to optimize the prevention of occupational accidents. The main purpose of this study was to analyse the safe behavior of the workers through the ABC model. This was an observational research using the cross-sectional design. The population was all workers (N=32) employed in the Production unit PT. X Mojokerto and the sample was the total population. The results of this study showed that most of workers (90,6%) had good knowledge; 84,4% of workers had good awareness; 84,4% of workers stated the need for safety had been fulfilled; all workers stated that the existing safety rules of the company had been implemented; 65,6% of workers never got positive reinforcement; 87,5% of workers never got punishment; and 87,5% of workers did safety behavior at the workplace. Keywords: production workers, safe behavior, The ABC model